2008
DOI: 10.3923/pjbs.2009.52.57
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Antibiotic, Probiotic and Prebiotic as Growth Promoters, on Growth Performance, CarcassCharacteristics and Hematological Indices of Broiler Chickens

Abstract: This experiment was conducted for comparison the effects of antibiotic (flavomycin), probiotic (primalac), prebiotic (Biolex-MB) and mixture ofprobiotic and prebiotic (primalac plus Biolex-MB) as dietary growth promoter on growth performance, carcass characteristics and hematological indices of broiler chickens. Three hundred day old Ross 308 broilers were equally distributed into 30 floor pens and reared for 42 day. A basal diet was formulated covering the recommendations of NRC (1994) for starter (0-21 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
69
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 33 publications
17
69
1
3
Order By: Relevance
“…These results are in agreement with those reported by Awad et al (2009). Many researchers have reported that probiotics and synbiotics enhance the performance of broilers by improving the intestinal morphology and microbial balance associated with suppressing pathogens and increasing the nutrient digestibility in the small intestine (Li et al, 2007;Ashayerizadeh et al, 2009). Birds that are experiencing chronic intestinal enteritis are in a constant mode of inflammation and recovery (Star et al, 2010).…”
Section: Resultssupporting
confidence: 83%
“…These results are in agreement with those reported by Awad et al (2009). Many researchers have reported that probiotics and synbiotics enhance the performance of broilers by improving the intestinal morphology and microbial balance associated with suppressing pathogens and increasing the nutrient digestibility in the small intestine (Li et al, 2007;Ashayerizadeh et al, 2009). Birds that are experiencing chronic intestinal enteritis are in a constant mode of inflammation and recovery (Star et al, 2010).…”
Section: Resultssupporting
confidence: 83%
“…European Commission banned four common ly used feed antibiotics: monensin sodium, salinomycin sodium, avilamycin, flavophospholipol (Banerjee, 1998). The banning of antibiotic growth promoter (AGP) will affect the poultry and livestock industry (Ashayerizadeh et al, 2009). To minimize the loss in growth, there is a need to find alternative to AGP.…”
Section: Introductionmentioning
confidence: 99%
“…Ashayerizadeh et al (2009) reported that prebiotics and probiotics as growth promoters can be used as alternatives for antibiotics because they improve growth performance of broiler chickens without any effect on consumers. Similar results for the improvement of growth performances have been reported by Sieo et al (2005); Apata (2008) and Yu et al (2008).…”
Section: Weekly Body Weight and Weight Gainmentioning
confidence: 99%